Competence committees: The steep climb from concept to implementation. Issue 9 (6th July 2021) - Acai, Anita; Cupido, Nathan; Weavers, Aliana; Saperson, Karen; Ladhani, Moyez; Cameron, Sharon; Sonnadara, Ranil R.
Abstract: Introduction: Competence committees (CCs) are groups of educators tasked with reviewing resident progress throughout their training, making decisions regarding the achievement of Entrustable Professional Activities and recommendations regarding promotion and remediation. CCs have been mandated as part of competency‐based medical education programmes worldwide; however, there has yet to be a thorough examination of the implementation challenges they face and how this impacts their functioning and decision‐making processes. This study examined CC implementation at a Canadian institution, documenting the shared and unique challenges that CCs faced and overcame over a 3‐year period. Methods: This study consisted of three phases, which were conceptually and analytically linked using Moran‐Ellis and colleagues' notion of 'following a thread.' Phase 1 examined the early perceptions and experiences of 30 key informants using a survey and semi‐structured interviews. Phase 2 provided insight into CCs' operations through a survey sent to 35 CC chairs 1‐year post‐implementation. Phase 3 invited 20 CC members to participate in semi‐structured interviews to follow up on initial themes 2 years post‐implementation. Detailed observation notes from 16 CC meetings across nine disciplines were used to corroborate the findings from each phase. Results: Response rates in each phase were 83% (n = 25), 43% (n = 15) and 60% (n = 12), respectively. Despite the high degree of support for CCs among faculty and resident members, several ongoing challenges were highlighted: adapting to programme size, optimising membership, engaging residents, maintaining capacity among members, sharing and aggregating data and developing a clear mandate. Discussion: Findings of this study reinforce the importance of resident engagement and information sharing between disciplines. Challenges faced by CCs are discussed in relation to the existing literature to inform a better understanding of group decision‐making processes in medical education. Future research could compare implementation practices across sites and explore which adaptations lead to better or worse decision‐making outcomes. Abstract : In this three‐year, multi‐method, study the authors uncover six key challenges (along with plausible solutions) that competence committees grapple with as they move from concept to implementation.